Peran Lembaga Adat Tolaki (LAT) Sulawesi Tenggara dalam Pelestarian Nilai-Nilai Budaya Suku Tolaki - Muh. Danil; Raemon Raemon (Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2023)
This research examines the role of the Tolaki Sultra customary institution in preserving the cultural values of the Tolaki tribe. This research reveals the problem of the role of customary institutions in preserving cultural values. This research focuses on the discussion of Tolaki, (1) What is the role of the Southeast Sulawesi customary institution (LAT) in preserving the cultural values of the Tolaki tribe. This research uses a qualitative method that aims to find out and explain the role of Southeast Sulawesi customary institutions (LAT) in preserving the cultural values of the Tolaki tribe with an ethnographic approach. This research was obtained through literature study, documentation, observation and interviews after data verification and starting with functional structure theory. Based on the field, it is known that the central board of the Tolaki customary institution (LAT) of Southeast Sulawesi, this research results in the existence of a customary institution (LAT) of Southeast Sulawesi in preserving the cultural values of the Tolaki tribe functions by preserving and developing the customs of the Tolaki tribe in activities that have been carried out one of them, preserving the mosehe wonua tradition, Tolea Pabitara training, training to recognize Kalosara, training in traditional marriage traditions, the process of implementing the Tolaki tribal cultural parade, then followed by the process of resolving Tolaki tribal customs are Omoapi (infidelity), elopement and conflict, the existence of the Tolaki Customary Institution in Southeast Sulawesi can run well.